Remuneração médica: uso de incentivos financeiros explícitos como indutor da mudança do cuidado na saúde suplementar - Carmen Lucia Soares Gomes (2010)
This work consists of two articles: a literature review of experiences with extrinsic incentive programs of a financial nature (otherwise known as pay for performance.) used in primary health care and a case study on the perception of a medical health operator, the use of financial incentives in a program for managing patients with cardiovascular disease (CMP). I review literature in journals indexed in major databases available online related to health sciences, using the portal of the Virtual Health Library - BIREME / PAHO / WHO, available at www.bireme.br to publications that took place between November 2005 and July 2009. I have chosen to read 26 articles, 15 of which (56%) were described as "positive" for demonstrating improvements in health with the use of incentives, while 08 other articles (28%) were described as "partially positive" and the remaining 03 (12%) were classified as "of no effect". The case study, in turn, relied on 23 semi-structured interviews (14 men and 09 women), conducted in September 2009 with both participating and non-participating doctors of the CMP, in respect of the actions implemented in 2008. Financial incentive is viewed as an important rather than a decisive factor determining the inclusion of patients into the program. The experiences and publications on the use of medical pay for performance are just beginning and their applications, development and effects need to be continually assessed.